Peru : Selected Issues. (IMF Staff Country Reports; Country Report, 2001)
This Selected Issues paper analyzes the developments in the labor market of Peru during the 1990s. The study assesses the relationship between the orientation of economic policy and export performance, in particular, export diversification over the last four decades. The paper describes the two-tier pension system and evaluates the long-term fiscal burden of this system. The study also reviews the design and implementation of monetary policy in Peru over the last decade.